Manajemen Kurikulum Pendidikan Anak Usia Dini di TK Smart Auladi - Fuadah Fuadah; Suklani Suklani (Journal on Education, 2024)
This research aims to describe how curriculum management is implemented in the Early Childhood Education of TK Smart Auladi. A qualitative approach is employed in this study, specifically through a case study method. Data collection techniques include interviews and documentation, focusing on curriculum-related documents such as weekly and daily lesson plans. The research aims to provide a clear description and overview of the management functions associated with the implementation of the early childhood education curriculum at TK Smart Auladi. The research methodology falls under the category of qualitative descriptive research. Data collection techniques involve observation, direct interviews, and documentation. Data analysis is conducted using an interactive model of analysis. Based on the results of data analysis, it can be concluded that the curriculum management functions at TK Smart Auladi encompass planning, implementation, and evaluation.